2017
DOI: 10.1007/s10903-017-0607-3
|View full text |Cite
|
Sign up to set email alerts
|

Healthful, Cultural Foods and Safety Net Use Among Cambodian and Brazilian Immigrant Communities in Massachusetts

Abstract: Declining health and food security status among low-income immigrants in the U.S. may result from limited access to healthful, cultural foods and safety net programs. We held focus group discussions with low-income Cambodian and Brazilian immigrants (11 groups, n = 84) living in Massachusetts. Cambodians and Brazilians valued healthful, cultural foods, emphasizing their beliefs that cultural foods are healthier and beneficial for weight management and aging. Although both groups could access these foods, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Cultivated own food to save money. Carney and Krause, 2020 (55) To examine the possibilities for engaged research oriented towards generating "healthy publics" and addressing food insecurity across disparate geo-graphical and political settings and amid structural and social constraints (29) (28) (30) To understand what makes it easier or harder for Latina mothers to provide their children with healthy food (53) (31) Unclear. Seattle, USA Qualitative; phenomenological A difference in access to fresh foods after migration, families from refugee camps reported greater access (54) To gather low-income community members' opinions about their food purchasing choices and their perceptions of the most effective ways to increase access to healthful foods in their communities Not specified.…”
Section: Collating Summarising and Reporting The Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cultivated own food to save money. Carney and Krause, 2020 (55) To examine the possibilities for engaged research oriented towards generating "healthy publics" and addressing food insecurity across disparate geo-graphical and political settings and amid structural and social constraints (29) (28) (30) To understand what makes it easier or harder for Latina mothers to provide their children with healthy food (53) (31) Unclear. Seattle, USA Qualitative; phenomenological A difference in access to fresh foods after migration, families from refugee camps reported greater access (54) To gather low-income community members' opinions about their food purchasing choices and their perceptions of the most effective ways to increase access to healthful foods in their communities Not specified.…”
Section: Collating Summarising and Reporting The Resultsmentioning
confidence: 99%
“…These supermarkets were often further away, requiring transportation (29) , and local stores were considered more expensive and of lower quality (32,56,59) . In order to acquire foods, participants typically visited several stores or food sources (27,32,47,49,53,56,58,60,82) particularly ethnic stores to supplement what they could procure at the supermarket. What are the rules related to food?…”
Section: Availability Of Specific Food Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…In interviews with Hispanic immigrant women in New York City, Park et al found they preferred foods that were fresh and unadulterated by processing or long periods of storage [61]. Cambodian and Brazilian immigrants in Massachusetts also focused on the freshness of their cultural foods [62]. Qualitative inquiry on the barriers to canned bean use may elicit other sociocultural reasons for their avoidance by Iowa Latinas [63].…”
Section: Discussionmentioning
confidence: 99%
“…Food insecurity and nutritional inadequacy among refugees have been recorded in a number of studies, including in the UK [ 21 ] and Australia [ 6 ], as well as in the USA [ 22 , 23 ] and Canada [ 24 , 25 ]. However, studies involving migrants/refugees from MENA countries were relatively few compared to those involving older immigrant populations or populations from other regions in the world (e.g., Liberians [ 22 ], and Cambodians and Brazilians [ 23 ] in the USA, and Latinos in Canada [ 24 ]). According to Asbu et al [ 15 ], there are gaps in knowledge about the health status of MENA migrants who have recently arrived in HICs.…”
Section: Introductionmentioning
confidence: 99%